2018
DOI: 10.3389/fneur.2018.00809
|View full text |Cite
|
Sign up to set email alerts
|

Tau Pathology in Parkinson's Disease

Abstract: Tau protein—a member of the microtubule-associated protein family—is a key protein involved in many neurodegenerative diseases. Tau pathology in neurodegenerative diseases is characterized by pathological tau aggregation in neurofibrillary tangles (NFTs). Diseases with this typical pathological feature are called tauopathies. Parkinson's disease (PD) was not initially considered to be a typical tauopathy. However, recent studies have demonstrated increasing evidence of tau pathology in PD. A genome-wide associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 85 publications
7
109
0
1
Order By: Relevance
“…The genetic association between the 17q21.31 locus and PD is therefore surprising. While it is not rare for tauopathy to occur alongside α-synuclein inclusions in the substantia nigra 37,38 , aggregated Tau is not a typical neuropathological feature of this disorder 36 . Despite the genetic association with 17q21.31, the OR is substantially smaller for PD than for PSP (OR ~ 1.4-1.5 for H1, OR ~ 0.8 for H2) 5,39 , and there does not appear to be any association with the H1c sub-haplotype 40,41 , indicating that different 17q21.31 locus variants and mechanisms may underlie the relative risk for each disease.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic association between the 17q21.31 locus and PD is therefore surprising. While it is not rare for tauopathy to occur alongside α-synuclein inclusions in the substantia nigra 37,38 , aggregated Tau is not a typical neuropathological feature of this disorder 36 . Despite the genetic association with 17q21.31, the OR is substantially smaller for PD than for PSP (OR ~ 1.4-1.5 for H1, OR ~ 0.8 for H2) 5,39 , and there does not appear to be any association with the H1c sub-haplotype 40,41 , indicating that different 17q21.31 locus variants and mechanisms may underlie the relative risk for each disease.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although p-Tau links to the pathogenesis of AD and other Tauopathies, recent studies have revealed that p-Tau has a relationship with PD. 46 MAPT (encoded Tau protein) gene mutation in humans increases the risk of PD, and Tau aggregation and filaments have been observed in familial PD. P-Tau is also a component of Lewy bodies, which suggests that p-α-Synuclein and p-Tau have shared pathways or synergistic effect in the PD progression.…”
Section: Introductionmentioning
confidence: 99%
“…This provides the rst evidence of an interaction between pesticide levels and rs11931074 of the SNCA gene on PD risk, although such a relationship has been demonstrated for the rs3775423 polymorphism and pesticide exposure [33]. The MAPT gene primarily encodes Tau protein, which is implicated in PD [34,35]. A study demonstrated that interaction between MAPT rs16940758 or rs2435211 and exposure to pesticides had no signi cant effect on PD either [33].…”
Section: Discussionmentioning
confidence: 81%